Educational Financing Management in Public Junior High ‎Schools in Deli Serdang Regency - Yenita Anggraini Barus; Amiruddin Siahaan; Abdurahman (JPI: Jurnal Pustaka Indonesia, 2026)
Educational financing management is central to school governance because it determines how financial resources are planned, implemented, evaluated, and communicated to support educational quality. This study aimed to analyze educational financing management at SMP Negeri 3 Pantai Labu and SMP Negeri 4 Percut Sei Tuan, Deli Serdang Regency, Indonesia, focusing on planning, implementation, evaluation, and transparency. Using a qualitative multi-site case study design, data were collected through in-depth interviews, field observations, and document analysis involving principals, vice principals, treasurers, administrative staff, school committee representatives, and teachers. Data were analyzed through condensation, coding, categorization, within-site analysis, cross-site comparison, and interpretive synthesis, with trustworthiness ensured through triangulation, member checking, peer debriefing, persistent observation, and audit trail documentation. The findings show that both schools used RKAS/ARKAS as the main instrument for aligning school needs, budget priorities, expenditure realization, accountability documents, and stakeholder communication. However, SMP Negeri 3 Pantai Labu adopted a conservative-stability model, while SMP Negeri 4 Percut Sei Tuan demonstrated a programmatic-adaptive model. This study implies that strengthening SOPs, treasurer competence, ARKAS literacy, program-based evaluation, and stakeholder communication is essential for improving accountable and quality-oriented school financing governance.